Teacher Attitudes Drive Eco-Literacy: Cultivating Environmental Understanding Through Educator Perspectives - Ranjan, Rajeev (Journal of Advanced Research in English & Education, 2024)
This article posits that teacher attitudes serve as a crucial catalyst in fostering ecological literacy among students. Eco-literacy, encompassing the knowledge, skills, and dispositions needed to understand and act upon environmental issues, is significantly shaped by the values and beliefs educators hold and project. This paper argues that teachers with positive and informed attitudes towards environmental sustainability are more likely to integrate environmental education effectively into their teaching practices, thereby influencing student engagement and learning outcomes in this critical domain. The article outlines ten key aspects through which teacher attitudes impact eco-literacy: teacher knowledge and preparedness, pedagogical approaches, integration of environmental themes, modeling sustainable behaviors, fostering student agency, creating supportive learning environments, addressing eco-anxiety, collaboration and professional development, engaging with the local environment, and advocating for environmental education. By examining these facets, the article underscores the importance of cultivating positive teacher attitudes towards environmental sustainability as a foundational element in promoting widespread eco-literacy among students.